Credit constraints and the international propagation of US financial shocks - Norbert Metiu; Björn Hilberg; Michael Grill (European Central Bank (ECB), 2016)
This paper investigates whether credit constraints in the US economy amplify the international propagation of US financial shocks. We model the dynamics of the US economy jointly with global macroeconomic and financial variables using a threshold vector autoregression. This model captures regime-specific dynamics conditional on the severity of credit constraints in the US economy. We identify three main episodes of tight credit in US financial history over the past thirty years. These occur in the late-1980s, in the early 2000s, and during the 2007-09 financial crisis. We find that US financial shocks are associated with a significant contraction in global economic activity in times of tight credit. By contrast, there is little impact of US financial shocks on the global economy in normal times. This asymmetry highlights an international dimension of the US financial accelerator mechanism.
Keywords: C32; C34; E32; G01; F44; 330; financial frictions; financial shocks; nonlinear dynamics; spillover